The general practice of Judo in the formation of self-concept, self-esteem and school performance in children of the first cycle of basic education - Marco Alexandre da Silva Batista; Sixto Cubo Cubo Delgado (Federación Extremeña de Balonmano; University of Extremadura, 2013)
This study aims to relate the practice of Judo with the formation of self-concept, self-esteem and school performance in students from lower primary. The sample has been composed of 531 Portuguese students of which 295 (55.6%) are children and 236 (44.4%) children, with an average of 9.13 years. From this sample, 394 subjects (74%) practiced at least one formal exercise extra-curricular character, and 96 students (24%) practiced Judo, with an experience of 9 months to 5 years, and graduations between white belt and green belt. As data collection instrument was used Self-Concept Scale Susan Harter validated for the Portuguese population (Martins, Peixoto, Mata, & Monteiro, 1995). Focus groups were developed with Judo coaches and officials education with the intention of evaluating opinions about the practice of Judo and its importance and relationship to the variables studied. The results show that the practice of judo promotes positive developments in the formation of self-concept and self-esteem, also improving school performance.